Dynamic microstructure evolution and mechanical properties of dilute Mg-Al-Ca-Mn alloy during hot rolling. (1st December 2022) - Xu, Shiwei; Zhu, Congcong; Lin, Zhanhong; Jin, Chen; Kamado, S.; Oh-ishi, K.; Qin, Yun
Highlights: The microstructure evolution of AXM050703 alloy was systematically studied. The interaction of 10–12 twins, 10–11 - 10–12 twins and kinks were studied. The multi-pass rolled samples with different microstructures were prepared. The strength of these rolled alloy (alloying elements only 1.5 wt.%) is higher than AZ31B. Abstract: The dynamic microstructure and texture of dilute Mg-0.50Al-0.71Ca-0.33Mn (wt.%) during hot rolling at two slab temperatures were investigated by electron backscattered diffraction (EBSD) and high resolution transmission electron microscopy (HRTEM). The results show that the development of the rolling microstructures is to first form 10–12 extension twins in the original grains, thereby forming the extension-twinned regions, and then to further form 10–11 - 10–12 double twins and kinks in the extension-twinned regions, and finally to form continuous dynamic recrystallized (continuous DRXed) grains in the double twins and the cross parts of the shear-deformed coarse extension-twinned regions. These extension twins, double twins and kinks show a decisive effect on the formation of rolling texture. The number of 10–11 - 10–12 double twins and resultant the continuous DRX process are strongly affected by the rolling slab temperature and the reduction thickness per pass. By optimizing the rolling conditions, texture and microstructures of the multi-pass rolled Mg-Al-Ca-Mn alloy sheets are successfully modified. Although the total alloy content is only 1.5 wt.%, these Mg-Al-Ca-Mn alloy sheets show much higher strength than the commercial Mg-3Al-1 Zn (wt.%) (AZ31B) sheet. Graphical abstract: Image, graphical abstract